Multimodality imaging methods and systemic biomarkers in classical low-flow low-gradient aortic stenosis: Key findings for risk stratification - Lopes, Maria Antonieta Albanez A. de M.; Campos, Carlos M.; Rosa, Vitor Emer Egypto; Sampaio, Roney O.; Morais, Thamara C.; de Brito Júnior, Fábio Sândoli; Vieira, Marcelo L. C.; Mathias, Wilson; Fernandes, Joao Ricardo Cordeiro; de Santis, Antonio; Santos, Luciano de Moura; Rochitte, Carlos E.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objectives The aim of the present study is to assess multimodality imaging findings according to systemic biomarkers, high-sensitivity troponin I (hsTnI) and B-type natriuretic peptide (BNP) levels, in low-flow, low-gradient aortic stenosis (LFLG-AS). Background Elevated levels of BNP and hsTnI have been related with poor prognosis in patients with LFLG-AS. Methods Prospective study with LFLG-AS patients that underwent hsTnI, BNP, coronary angiography, cardiac magnetic resonance (CMR) with T1 mapping, echocardiogram and dobutamine stress echocardiogram. Patients were divided into 3 groups according to BNP and hsTnI levels: Group 1 (n = 17) when BNP and hsTnI levels were below median [BNP < 1.98 fold upper reference limit (URL) and hsTnI < 1.8 fold URL]; Group 2 (n = 14) when BNP or hsTnI were higher than median; and Group 3 (n = 18) when both hsTnI and BNP were higher than median. Results 49 patients included in 3 groups. Clinical characteristics (including risk scores) were similar among groups. Group 3 patients had lower valvuloarterial impedance (P = 0.03) and lower left ventricular ejection fraction (P = 0.02) by echocardiogram. CMR identified a progressive increase of right and left ventricular chamber from Group 1 to Group 3, and worsening of left ventricular ejection fraction (EF) (40 [31–47] vs. 32 [29–41] vs. 26 [19–33]%; p < 0.01) and right ventricular EF (62 [53–69] vs. 51 [35–63] vs. 30 [24–46]%; p < 0.01). Besides, there was a marked increase in myocardial fibrosis assessed by extracellular volume fraction (ECV) (28.4 [24.8–30.7] vs. 28.2 [26.9–34.5] vs. 31.8 [28.9–35.5]%; p = 0.03) and indexed ECV (iECV) (28.7 [21.2–39.1] vs. 28.8 [25.4–39.9] vs. 44.2 [36.4–51.2] ml/m2, respectively; p < 0.01) from Group 1 to Group 3. Conclusions Higher levels of BNP and hsTnI in LFLG-AS patients are associated with worse multi-modality evidence of cardiac remodeling and fibrosis.